(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to identify the impact of the educational strategy, differentiation, and aids in developing some components of perceptual-motor anticipation and offensive skills for basketball juniors. Knowing the difference between the advantage of the impact of the education strategy, differentiation between using educational aids and not using them in developing perceptual-motor anticipation and offensive skills for basketball juniors. Therefore, the researchers used the experimental method with two equal groups to suit the nature of the research problem. The research population was determined from second-year intermediate students at Baqir Al-Suhail Secondary School in the Baghdad Al-Karkh Education Directorate 3, with an average age of (15-16) years, and they numbered (58) students divided into two sections, the first of which was 28 and the second number 30. After that, the researchers determined the research sample in a systematic random way by adopting 22 students as a sample for the two research groups (they were equal), constituting a percentage of (37.93). They were divided in a random way and by lottery into two groups with (11) players for each group, an experimental group. Differentiated learning uses educational means and a control group (the method followed). The researchers resorted to codified scientific research procedures, including determining the dependent variables and testing them. After that, they conducted a pre-test. After that, educational units were prepared according to the strategy of differentiated learning using educational means, with a total of 20 educational units (two units). per week) for a period of 45 minutes, after which the post-test was conducted and the researchers intended to use the statistical package that led them to important results that led to the most important conclusions, including: Differentiated education strategy is education that aims to raise the level of all students, not just students who face problems in predicting motor or skill perception. It takes into account the individual’s characteristics and previous experiences. The continuing education strategy has an effective impact on improving the components of students’ motor awareness and offensive basketball skills. Educational methods, according to the differentiated education strategy, have a positive role and impact on transferring knowledge, consolidating awareness, increasing learners’ experiences and skills, and developing their attitudes in an exciting atmosphere and a firm desire for better learning. There is a positive relationship between anticipating motor awareness and the attack that a basketball player must master, as players learn how to anticipate the opponent’s movements and extract important motor information. The research recommendations emphasize the application of the differentiated education strategy as it is an educational strategy that takes into account the needs of each individual student and ensures the provision of support. What is necessary to raise the level of expectation of motor awareness and skills for everyone, with a focus on enhancing the previous experiences of each student. By enhancing the use of educational methods that are compatible with the differentiated education strategy, focusing on its role in effectively transferring knowledge, stabilizing awareness and increasing learners’ experiences and skills, through designing stimulating and interesting educational environments.